The Relationship Between Free Nutritious Food Consumption (MBG) and Students' Focus on Learning in the Last Hour at SMAN 4 Bima City - Abbas, Ibnu; Akhyar, Akhyar; Ilham, Ilham; Hasanah, Uswatun; Humaidin, Humaidin; Haeruddin, Haeruddin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Decreased student focus during the final period of class is a pedagogical challenge influenced by various factors, such as physical fatigue and mental saturation. This study aims to analyze the relationship between the consumption of Free Nutritious Meals (MBG) and student focus at SMAN 4 Kota Bima, and to identify factors that influence the effectiveness of this nutritional support. Using a descriptive qualitative approach with a case study method, data were collected through in-depth interviews with educators and field observations. The results showed that the MBG program made a positive contribution to maintaining energy stability and cognitive responsiveness of students compared to students who did not consume it. Students who received MBG appeared calmer, more ready to learn, and able to maintain concentration longer during critical school hours. However, the effectiveness of MBG is not fully optimal because it is influenced by multidimensional variables such as nutritional menu variations, students' rest patterns at home, and the teaching methods used by teachers. The study concluded that although MBG provides a strong physical foundation, significantly improving learning focus requires a synergy between varied nutrition, a healthy lifestyle, and interactive pedagogical innovations in the classroom.